2009
DOI: 10.1590/s1413-78522009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Osteointegração de enxertos liofilizados impactados

Abstract: Acta Ortop Bras. 2009; 17(2):24-8 analysis was based on Merle, d'Aubigné and Postel's scores; while the radiographic analysis was based on an established score for radiographic bone incorporation. Results: No clinical or radiographic differences were found between the groups, and both groups showed an overall osteointegration rate of 85% both in the acetabular and in the femoral component. Conclusions: Impacted lyophilized human and bovine bone grafts produced by following to the proposed protocol did not caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Em amostras cúbicas, o comprimento varia entre 88 e 100 mm, com largura de 8 a 30 mm e espessuras de 2 a 15 mm. 2,5,21,24 As amostras cilíndricas variam menos e têm entre 10 e 8 mm. 25,26 Com base nesses estudos, escolhemos diferentes tamanhos de amostra para orientar o real significado, já que essa característica pode influenciar o resultado do procedimento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em amostras cúbicas, o comprimento varia entre 88 e 100 mm, com largura de 8 a 30 mm e espessuras de 2 a 15 mm. 2,5,21,24 As amostras cilíndricas variam menos e têm entre 10 e 8 mm. 25,26 Com base nesses estudos, escolhemos diferentes tamanhos de amostra para orientar o real significado, já que essa característica pode influenciar o resultado do procedimento.…”
Section: Discussionunclassified
“…30,31 O processo de autoclave, que prevê a aplicação de temperatura superior a 120°C para exterminar riscos de infecção ao receptor, pode ser utilizado como opção de esterilização. 2,14,21,26,27 Em contrapartida, esse processo reduz significativamente a resistência mecânica do enxerto ósseo. 14 Ainda não há consenso sobre o melhor método para esterilização de ossos liofilizados.…”
Section: Discussionunclassified
“…Due to limited availability of fresh-frozen allografts in our department, we have started research and development of a bone bank with freeze-dried bovine bone grafts (Galia et al 2009a ; Galia et al 2009b ; Macedo et al 1999 ). In the medical literature, there are only a few studies describing the use of xenografts (Laurencin and El-Amin 2008 ; Zabeu and Mercadante 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The need to use large quantities of bone graft in hip surgeries at our department encouraged research and use of bone substitutes, specifically freeze-dried bovine xenografts (Galia et al 2009a ; Macedo et al 1999 ). The bovine bone is considered a natural hydroxyapatite with chemical composition, porosity, size and shape similar to the human bone, providing structural and osteoconductive support for new bone formation (Galia et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…No study has shown an association between lyophilized xenografts and the presence of reaction or infection (Ledford et al 2013;Shibuya et al 2012), as well as the association between the use of this kind of graft and the bovine spongiform encephalopathy disease (BSE) and its new variant the Creutzfeldt Jakob disease (CJD). The secure use of this graft in relation to the CJD becomes possible because the lyophilization process chemically inactivates most of the bacterial agents, viral agents and prionic (prions) agents to a safe limit to the use in humans (Galia et al 2009b;Rosito et al 2008;Wenz et al 2001), making the bovine graft safe for use in humans. Xenografts are an excellent graft option, considering the good clinical outcomes, consolidation, absence of pain, and absence of antigenic reaction (Maffulli et al 2013;Morax et al 1993;Rosito et al 2008).…”
Section: Discussionmentioning
confidence: 99%